Gen Z’s Motivations and Expectations for Digital Game Development in Indonesia - Wibowo, Tony; Kho, Mega Hardianti; Tan, Dennis Sidartha; Cen, Li (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
The rapid growth of Indonesia’s digital economy positions the gaming industry as a key driver of innovation and sustainable engagement. This study analyzes the motivations and expectations of Gen-Z in playing video games and examines how tech driven innovation including Artificial Intelligence (AI) and Internet of Things (IoT) enhances user experience and digital sustainability. Using an exploratory sequential design, the research combines qualitative exploration with quantitative correlation analysis through SPSS software. The results reveal that achievement motivation significantly correlates with expectations for rewards, exploration, and skill development; escapism motivation relates to expectations of immersive experiences; and social motivation correlates with expectations for interactive and emotionally engaging features. These relationships highlight how Gen-Z values both personal accomplishment and meaningful digital interaction. The findings demonstrate that Gen-Z’s gaming behavior is not solely for entertainment but also represents technology-enabled engagement supporting sustainable digital ecosystems. The study offers strategic insights for game developers, educators, and policymakers to leverage technology in fostering creativity, collaboration, and growth aligned with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure).